ANALSIS KEWENANGAN WAKIL BUPATI DALAM PENYELENGGARAAN PEMERINTAH DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 9 TAHUN 2015 TENTANG PERUBAHAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAH DAERAH - Eva lestari; Mukhlis M; Yusrizal Y (Fakultas Hukum Universitas Malikussaleh, 2021)
ABSTRACT This study aims to explain the authority and obstacles of the Deputy Regent in administering local government based on Law Number 9 of 2015 concerning Amendments to Law Number 23 of 2014 concerning Regional Government. The Deputy Regent's authority is not regulated in detail in Law Number 9 of 2015 concerning Amendments to Law Number 23 of 2014 concerning Regional Government, causing the assumption that the Deputy Regent is only a symbol. This research uses normative juridical research using a conceptual approach, descriptive and prescriptive research form. This research uses premier legal material in the form of Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 of 2014 concerning Regional Government. Based on the results of the analysis, it is known that the Deputy Regent's authority in the administration of regional government is to assist, monitor, coordinate, follow up, carry out efforts, evaluate, and provide advice to the Regent. Carry out the duties and authorities of the Regent if the Regent is serving a period of detention or is temporarily absent. Carry out other government duties and obligations given by the Regent as determined by the Regent's decision, and carry out tasks with the Regent until the end of the term of office. Obstacles to the Deputy Regent in exercising his authority based on Law Number 9 of 2015 concerning the Second Amendment to Law Number 23 2014 concerning Regional Government that; weak laws and regulations regarding the working relationship between the Regent and Deputy Regent political ethics, the lack of the role of the Deputy Regent, accountability of the Deputy Regent to the Regent, and disharmony between the Regent and the Deputy Regent Keywords: Authority, Deputy Regent, Local Government Administration